Test-Taker Perceptions of Global and Local English Proficiency Tests: Evidence from Indonesian EFL Higher Education - Sony, Ahmad; Anam, Syafiul; Munir, Ahmad (Universitas Islam Negeri Sunan Ampel Surabaya, 2026)
This study examines test-taker perceptions of global and local English proficiency tests, focusing on suitability, preparation, and engagement. Although previous studies have explored English proficiency testing from policy or outcome-based perspectives, limited research has integrated test suitability with preparation processes and emotional engagement from the learners' viewpoint. Using a basic interpretative qualitative design, data were collected through interviews with test-takers who had experience with both global and local English proficiency tests. This study contributes to language assessment research by offering an integrated learner-centered account of how experiences with global and local English proficiency tests shape test suitability, preparation processes, and emotional engagement. The findings indicate that test-takers perceived suitability as a contextual fit rather than an inherent test quality. Global tests were viewed as appropriate for international academic and professional goals due to their recognition, but were also considered demanding and emotionally challenging. In contrast, local tests were perceived as more suitable for institutional purposes due to their familiarity and alignment with the context. These perceptions shaped preparation strategies and engagement. Overall, the study highlights the central role of test-taker perceptions in shaping test experiences and suggests the need for assessment practices that balance global recognition with local relevance.